Peran elemen fisik kota dalam pembentukan citra sebagai kota kreatif - Edy Abdurrahman Syahrir; Retno Widodo Dwi Pramono (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2021)
Several creative cities aim at becoming tourist destinations, due to the support of physical elements supported by visual identity. Furthermore, due to the low number of tourist visits, most cities have optimally embraced creativity during development, thereby making it a driving force for its citizens' welfare. Therefore, this research aims to identify the physical elements as associated with the image formation of Pekalongan City based on the assessments of residents and visitors. This is a deductive research with the quantitative and qualitative method used for analysis and data were obtained from primary and secondary sources. Primary data were collected through observation, questionnaires, and interviews, while secondary were obtained from literature studies and content searches on the internet. The results showed that the design of a city's physical element through cultural works and folk arts, create unique attributes that attract tourists. Furthermore, these results are expected to encourage city planners and designers to help city managers to understand the importance and uniqueness of visual image for branding formation in an effort to strengthen its competitiveness and attract tourists.